THE DECISION SUPPORT SYSTEM OF PUBLIC SERVICE SATISFACTION USING TOPSIS METHOD AT REGIONAL I BKN YOGYAKARTA - Benedictus Fredika Apriawan Santoso; Indah Susilawati (Informatika, Universitas Jenderal Soedirman, 2021)
Public service satisfaction is the result of public opinion and assessment for the service performance provided by the public service organizer apparatus. In real action, this public satisfaction survey is conducted periodically to discover the real value owned and anything that the public wants to get for its services. This then becomes one of the commitments of the Regional I BKN Yogyakarta in implementing the predetermined quality policies and service standards which are useful for improving the service quality for the public. Hence, additional efforts are needed in processing the data obtained from the public satisfaction survey report results to follow up according to the real requirements expected by the public in making decisions, so that they can be right on target. Researchers aim to make a decision support system prototype that gives an overview about the public service satisfaction rate, using the TOPSIS Method with the parameter data of satisfaction criteria and the survey data as well as the value range of the public service satisfaction survey in January to March 2019. Based on the data of the public service satisfaction test for that 3 months, either the results of the system prototype calculation or the manual calculation, 3-period compatibility with 100% was obtained.